2007
DOI: 10.1504/gber.2007.015101
|View full text |Cite
|
Sign up to set email alerts
|

Foreign direct investment and economic growth: some evidence from across the world

Abstract: This study is concerned about foreign direct investment (FDI) and economic growth across the world for the period of 1991-2001. This article produces fresh empirical evidence on the relation between FDI and economic growth obtained from single-equation and simultaneous equation estimates for 140 countries using macro economic variables. The results indicate that a positive and statistically significant estimate of coefficient of FDI is obtained from single equation ordinary least squares method for real per-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…For instance, Cuadros, Orts and Alguacil (2004), who used a trivariate vector autoregressive regression (VAR) model, found evidence of the FLGH in Mexico and Argentina but not in Brazil. Other findings that corroborate the FLGH can be found in Basu, Chakraborty and Reagle (2003), Hermes and Lensink (2003), Makki and Somwaru (2004), Li and Liu (2005), Lensink and Morrissey (2006), Ghatak and Halicioglu (2007), Batten and Vo (2009), and Alfaro, Areendam, Sebnem and Selin (2010). The cross-sectional study by Makki and Somwaru (2004), who used the three stage least squares (TSLS) estimation method, found a strong, positive interaction between FDI and trade, which in turn encouraged economic growth.…”
Section: Literature Reviewmentioning
confidence: 52%
“…For instance, Cuadros, Orts and Alguacil (2004), who used a trivariate vector autoregressive regression (VAR) model, found evidence of the FLGH in Mexico and Argentina but not in Brazil. Other findings that corroborate the FLGH can be found in Basu, Chakraborty and Reagle (2003), Hermes and Lensink (2003), Makki and Somwaru (2004), Li and Liu (2005), Lensink and Morrissey (2006), Ghatak and Halicioglu (2007), Batten and Vo (2009), and Alfaro, Areendam, Sebnem and Selin (2010). The cross-sectional study by Makki and Somwaru (2004), who used the three stage least squares (TSLS) estimation method, found a strong, positive interaction between FDI and trade, which in turn encouraged economic growth.…”
Section: Literature Reviewmentioning
confidence: 52%
“…Many empirical studies have tried to explain the relationship between FDI and growth (Ozturk, 2007). In most of these studies, the researchers found that FDI has a positive effect on growth (Alfaro, Chanda, Kalemli-Ozcan, & Sayek, 2010; Basu, Chakraborty, & Reagle, 2003; Batten & Vo, 2009; Campos & Kinoshita, 2002; Ghatak & Halicioglu, 2007; Hansen & Rand, 2006; Hermes & Lensink, 2003; Lensink & Morrissey, 2006; Li & Liu, 2005; Makki & Somwaru, 2004). In many studies dealing with subsets of the countries, FDI or FDI in combination with some other factor or factors is positively related to growth, while several studies (Chakraborty & Basu, 2002; Chowdhury & Mavrotas, 2003; Dhakal, Rahman, & Upadhyaya, 2007) have found no significant relationship between FDI and growth.…”
Section: Review Literaturementioning
confidence: 99%
“…There is a solid causal association among FDI and GDP for 31 non-industrial countries for time span ranges from 1970 to 2000. FDI has a positive development influence when the nation has fundamentally prepared a workforce that awards it to mishandle FDI floods [29,30]. FDI has positive and tremendous ramifications for the genuine per capita GDP for a panel of 140 nations [30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…FDI has a positive development influence when the nation has fundamentally prepared a workforce that awards it to mishandle FDI floods [29,30]. FDI has positive and tremendous ramifications for the genuine per capita GDP for a panel of 140 nations [30]. FDI has a positive and gigantic effect on economic development for nations with large salaries [4].…”
Section: Literature Reviewmentioning
confidence: 99%